A novel approach for contactless heart rate monitoring from pet facial videos - Hu, Renjie; Gao, Yu; Peng, Guoying; Yang, Hongyu; Zhang, Jiajin (Frontiers in Veterinary Science, 2024)
IntroductionMonitoring the heart rate (HR) of pets is challenging when contact with a conscious pet is inconvenient, difficult, injurious, distressing, or dangerous for veterinarians or pet owners. However, few established, simple, and non-invasive techniques for HR measurement in pets exist.MethodsTo address this gap, we propose a novel, contactless approach for HR monitoring in pet dogs and cats, utilizing facial videos and imaging photoplethysmography (iPPG). This method involves recording a video of the pet’s face and extracting the iPPG signal from the video data, offering a simple, non-invasive, and stress-free alternative to conventional HR monitoring techniques. We validated the accuracy of the proposed method by comparing it to electrocardiogram (ECG) recordings in a controlled laboratory setting.ResultsExperimental results indicated that the average absolute errors between the reference ECG monitor and iPPG estimates were 2.94 beats per minute (BPM) for dogs and 3.33 BPM for cats under natural light, and 2.94 BPM for dogs and 2.33 BPM for cats under artificial light. These findings confirm the reliability and accuracy of our iPPG-based method for HR measurement in pets.DiscussionThis approach can be applied to resting animals for real-time monitoring of their health and welfare status, which is of significant interest to both veterinarians and families seeking to improve care for their pets.